Association between serum zinc and serum neurofilament light chains: A population-based analysis. - Jun Wei; Ye Xu; Yang Liu (PLoS ONE)
Background While serum zinc levels are strongly associated with various neurological disorders, the relationship between serum zinc and axonal damage remains largely unexplored. Consequently, the objective of this study was to investigate whether an association exists between serum zinc levels and serum neurofilament light chain (sNfL) concentrations in the general population. Methods Data from the National Health and Nutrition Examination Survey (NHANES) conducted during 2013-2014 were utilized for this study. We applied multiple linear regression and smoothed curve fitting methods to explore the connection between serum zinc levels and sNfL. Furthermore, subgroup analyses and interaction tests were performed to assess the consistency of this association among various populations. Results This analysis included a total of 585 adults. After controlling for various confounding variables, we identified a significant negative association between serum zinc levels and sNfL (β = -0.62, 95% CI: -1.18, -0.05, p = 0.0321). Stratified analyses revealed that this negative association was significant only among individuals who were divorced, widowed, or separated, with no such association observed in other subgroups. This finding suggests that serum zinc levels may have a more pronounced impact on neurological health within these specific populations. Additionally, we identified an L-shaped association between serum zinc and sNfL, with an inflection point at 10.21 nmol/L. Conclusion Our findings demonstrate an inverse association between serum zinc levels and sNfL concentrations among adults in the United States. This relationship is particularly pronounced in individuals who are divorced, widowed, or separated.